Across the narrow sea: A Transnational Approach to Anglo-Dutch Travelogues. Issue 1 (2nd January 2020) - van Raamsdonk, Esther; Moss, Alan
ABSTRACT: The busy traffic between England and the United Provinces in the seventeenth century produced travel literature by merchants, scholars, soldiers, and diplomats. What can these sources tell us about commonalities and differences among these travellers and between the nations? This article provides a case study of a transnational approach, setting Dutch and English accounts side by side to enrich our understanding of how travellers sought out specific sites and institutions. Strikingly, travellers reported on similar themes, such as royalty, universities and war, yet were also keen to draw contrasts with the visited country. We show how these patterns of travel and imagery can throw light on Anglo-Dutch relations, providing us with the personal nuance often absent from official texts. Simultaneously, Anglo-Dutch relations affected the destinations and outlooks of travellers. The contribution of this article is its presentation of new material in an Anglo-Dutch framework.